Next‐Generation Polymeric Nanomedicines for Oncology: Perspectives and Future Directions. Issue 18 (7th August 2020) - Fletcher, Nicholas L.; Kempe, Kristian; Thurecht, Kristofer J.
Abstract: Precision polymers as advanced nanomedicines represent an appealing approach for the treatment of otherwise untreatable malignancies. By taking advantage of unique nanomaterial properties and implementing judicious design strategies, polymeric nanomedicines are able to be produced that overcome many barriers to effective treatment. Current key research focus areas anticipated to produce the greatest impact in polymer applications in nanomedicine for oncology include new strategies to achieve "active" targeting, polymeric pro‐drug activation, and combinatorial polymer drug delivery approaches in combination with enhanced understanding of complex bio‐nano interactions. These approaches, both in isolation or combination, form the next generation of precision nanomedicines with significant anticipated future health outcomes. Of necessity, these approaches will combine an intimate understanding of biological interactions with advanced materials design. This perspectives piece aims to highlight emerging opportunities that promise to be game changers in the nanomedicine oncology field. Discussed herein are current and next generation polymeric nanomedicines with a focus towards structures that are, or could, undergo clinical translation as well as highlight key advances in the field. Abstract : Next‐generation polymeric nanomedicines represent a potential step‐change in therapeutic approaches and outcomes for currently difficult to treat malignancies. This perspective highlights key developments and areas for potential impact in cutting‐edge approaches to the synthesis and study of polymeric nanomedicines. It is focussed on key areas including new strategies for tumor targeting, pro‐drug activation and combinatorial therapeutic approaches.